Depostition of platinum-ruthenium alloy by using lyotropic liquid crystalline template. - Nur Liyana Jakfar Alkhatib. (2010)
Hexagonal mesoporous Pt-Ru alloy was successfully synthesized by electrodeposition onto a conductive indium-tin oxide (ITO) glass plate utilizing a lyotropic liquid crystalline (LLC) template prepared using a non-ionic surfactant and salts of Pt and Ru. Polarized optical microscopy (POM) studied phase changes of the LLC template as a heater was used to gradually reduce temperature. The temperature at which hexagonal structures exist was used to synthesize Pt-Ru alloy. The resulting material was studied for its catalytic performance using cyclic voltammetry (CV) while its surface morphology is characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM). By varying the electrodeposition run time, analysis between performance and film thickness was performed. Pt-Ru synthesized from the experiment was characterized to obtain results which were in-line with published results. An average particle size distribution of about 50 nm was achieved with the correct composition and hexagonal structures as template by LLC. It was worthy to note that the thickest film did not give the best catalytic performance but rather, most importantly is the optimization between film thickness and catalytic performance.